Proteome changes associated with the remote germination in carnaúba (Copernicia prunifera) seeds - Sheheryar (2023)
The carnauba palm (Copernicia prunifera), a member of the Arecaceae family, acquires a characteristic way of protecting its embryonic tissues during its early organogenesis by adopting a tubular type of remote germination. This palm has great ecological and socioeconomic significance because every part of it can be used: the roots are therapeutic and have medicinal value; the leaves are used to make textiles and handicrafts; and the most crucial production of wax is by its younger leaves, which are used in cosmetics, electronics, pharmaceutical capsules, coatings, and polishing waxes and generate more than $55 million annually. Therefore, understanding its germination and mobilization of seed reserves is fundamental to establishing biotechnological strategies to increase the production and utilization range of this well-known “tree of life." The objective of the current study was to determine the spatiotemporal changes in the proteome of haustorium and cotyledonary petiole guided by morphoanatomical alterations during emergent organogenesis. The haustorium and cotyledonary petiole were evaluated morphoanatomically during germination, and four stages (the mature embryo, 2, 5, and 10 days after germination) were selected for proteomic analysis. The morphoanatomical analysis revealed that, after germination, the embryonic axis continues to divide, organogenesis occurs inside the emerging cotyledonary petiole, and the plant body ascends from the cotyledonary petiole with developed leaves and a complex root system. Samples from both tissues’ stages were submitted to the bottom-up proteomics approach, where the peptides were analyzed in an nLC-MS/MS Orbitrap system. Proteome Discoverer v. 2.5 was used for the protein and peptide identifications, and Perseus v. 1.6.14 was used for the statistical analysis of the quantitative data. In proteomics analysis, 4776 and 4473 proteins were identified in the cotyledonary petiole and haustorium, respectively. In a total of 1673 up-regulated proteins in the haustorium, cellular catabolic processes, carbohydrate and lipid metabolic processes, and carbohydrate derivative biosynthesis activities were identified in GOBP, catalytic activity, peptidase activity, and hydrolase activity were identified in GOMF. Whereas, 318 differentially abundant proteins in the cotyledonary petiole, in particular, developmental growth, cell growth, and metabolic processes involving carbohydrate derivatives were found in GOBP, whereas catalytic activity, lyase activity, fructokinase activity, and cytoskeleton structural components were common in GOMF. Additionally, in the cotyledonary petiole, we quantified proteins involved in lipids, and protein mobilization, along with proteins involved in the biosynthesis of growth regulators such as salicylic acid (SA), jasmonic acid, ethylene, indole-3-acetic acid (IAA), cytokinin, and gibberellins (GA), which play a pivotal role in plant growth and development. This work shows that the haustorium plays a pivotal role in the synthesis of hydrolases and transports the reserve to the seedling, whereas the embryonic axis continues its growth and development inside the cotyledonary petiole by utilizing these reserves and the action of other essential proteins responsible for growth and development.